Quality Improvement for Cardiovascular Disease Care in Low- and Middle-Income Countries: A Systematic Review - Lee, Edward S. (PLoS One, 2016)
BACKGROUND: The majority of global cardiovascular disease (CVD) burden falls on people living in low- and middle-income countries (LMICs). In order to reduce preventable CVD mortality and morbidity, LMIC health systems and health care providers need to improve the delivery and quality of CVD care. OBJECTIVES: As part of the Disease Control Priorities Three (DCP3) Study efforts addressing quality improvement, we reviewed and summarized currently available evidence on interventions to improve quality of clinic-based CVD prevention and management in LMICs. METHODS: We conducted a narrative review of published comparative clinical trials that evaluated efficacy or effectiveness of clinic-based CVD prevention and management quality improvement interventions in LMICs. Conditions selected a priori included hypertension, diabetes, hyperlipidemia, coronary artery disease, stroke, rheumatic heart disease, and congestive heart failure. MEDLINE and EMBASE electronic databases were systematically searched. Studies were categorized as occurring at the system or patient/provider level and as treating the acute or chronic phase of CVD. RESULTS: From 847 articles identified in the electronic search, 49 met full inclusion criteria and were selected for review. Selected studies were performed in 19 different LMICs. There were 10 studies of system level quality improvement interventions, 38 studies of patient/provider interventions, and one study that fit both criteria. At the patient/provider level, regardless of the specific intervention, intensified, team-based care generally led to improved medication adherence and hypertension control. At the system level, studies provided evidence that introduction of universal health insurance coverage improved hypertension and diabetes control. Studies of system and patient/provider level acute coronary syndrome quality improvement interventions yielded inconclusive results. The duration of most studies was less than 12 months. CONCLUSIONS: The results of this review suggest that CVD care quality improvement can be successfully implemented in LMICs. Most studies focused on chronic CVD conditions; more acute CVD care quality improvement studies are needed. Longer term interventions and follow-up will be needed in order to assess the sustainability of quality improvement efforts in LMICs.